SARS-CoV-2 Proteases: Role and Potential as Drug Target - Swestikaputri, Chrecentia Hanna; Sudiro, Tjahjani Mirawati (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2023)
The coronavirus disease of 2019 (COVID-19) has become a long global pandemic caused by a transmitted and pathogenic virus called Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Even though WHO has retracted the global emergency status of COVID-19, it remains a threat. Various antiviral treatments are being devised and developed due to the coronavirus's high rate of mutation and need to create more effective treatments for infections. Protease is an important part of the life cycle of SARS CoV-2 hence it is intended as an antiviral target. Several protease inhibitor candidates have been identified, but there is still much to learn, including the structure and mechanism by which these inhibitors inhibit protease. This article investigates the function of proteases in the SARS CoV-2 life cycle and the mechanism of protease inhibition. Past and present research on the protease inhibitor mechanism of action was evaluated in order to generate this literature review. Here we found that the main protease (Mpro), one of SARS-CoV's proteases, is highly conserved among coronaviruses and has no human homolog. As a result, numerous Mpro inhibitors have been developed in an effort to treat COVID-19. PAXLOVID, an Mpro inhibitor, is already approved by FDA for emergency use.